Litter dynamics in post-fire successional forests of Quercus ilex - FERRAN, A.; Vallejo, V. R. (Plant Ecology, 1992)
Forest floor regeneration after fire in a holm oak forest was studied in a chronosequence in Catalonia (NE Spain). The sampled area represented situations of high fire disturbance because of the frequency of wildfires and the high impact of erosive processes. Forest floor bulk samples from the L, F and H layers were taken in 5 burned plots, aging from 0 to 35 years. They were analyzed for dry standing weight, and organic carbon and N content. Plant cover reached almost 100°o two years after the fire. During the first 20 years, shrubs and herbs had the highest surface covering, and thereafter, holm oaks became dominant. Holm oak litterfall stabilized by the fourth year after burning. The major shrub species which were present in the chronosequence had two different patterns with respect to nitrogen: 1) a low litter C/N ratio (i.e. nitrogen fixing species); 2) a high litter C/N ratio. The litter decay coefficients were relatively high, allowing for a rapid structuration and formation of the L and F layers after the fire. Indeed, 95 ° o of the maximum steady standing weight accumulates in 8-9 years. The pattern of cover in the different strata influenced the lateral distribution and variable accumulation of the forest floor layers and determined different turnover rates.
Keywords: C/N ratio; Decay coefficient; Holm oak; mediterranean forest; plant regeneration

SOIL EVOLUTION AFTER FIRE IN QUERCUS-ILEX AND PINUS-HALEPENSIS FORESTS - FERRAN, A.; SERRASOLSAS, I.; Vallejo, V. R. (RESPONSES OF FOREST ECOSYSTEMS TO ENVIRONMENTAL CHANGES, 1992)
Four contrasted burned sites in Catalonia (NE Spain) have been compared to-illustrate the diversified response to fire depending on the interaction of substrate-vegetation characteristics. Data from plant cover evolution, forest floor layers and soil chemical properties demonstrated that the garrigue on limestone is the most resilient ecosystem as a result of the resprouting capacity of Ouercus coccifera and the high soil stability. The shrubland on marls was however, the least resilient, with the poorest plant regeneration and greatest erosion rates. The plant communities on conglomerates and the holm oak forest on schists, represented intermediate situations, where the variable degree of erosion and nutrient losses were compensated by a rapid plant colonization just after the fire.
The following values have no corresponding Zotero field: periodical: RESPONSES OF FOREST ECOSYSTEMS TO ENVIRONMENTAL CHANGES pub-location: BARKING ESSEX
Keywords: burned sites; ecosystem resilience; fire; Quercus coccifera; Quercus ilex; Shrubland; Spain